O realizador e a personagem: relações intersubjetivas no processo criativo do documentário - Pereira, Irislane Mendes (2011)
This thesis aims at the study of the relations between the documentarian and his character. More specifically, it analyses the dialogue that is established between both parts. Underpinned by theories and concepts by Brazilian and foreign documentary genre scholars Fernão Pessoa Ramos, Jean-Claude Bernardet and Bill Nichols , this work also examines the matter of the production of the documentary s truth, as such a meeting intermediated by the camera and proposed to a spectatorial reading could guarantee it. Inseparable from this first interrogation, there is a second one that refers to the witnessing subject s freedom and to the ethics of these exchanges. The selection of the corpus privileged those films which characters seem to have their singularities preserved in the situation of interaction in which they are engaged. Parallel to that and opportunely, a brief history of the documentary in Brazil, under the influx of Italian neorealism, direct cinema and cinema vérité, which molded in it its most remarkable features, is presented. Methodologically, it is a documental and bibliographical research. As a result, it is possible to assure that the corpus analysis especially of these two important examples of this genre, Viramundo (1965), by Geraldo Sarno, and Jogo de Cena (2007), by Eduardo Coutinho has evinced different models that present actors have to convey with words